A sikeres város - Enyedi, György (Tér és Társadalom, 1997)
Recently, each urban seftlement is involved in the international competition of cities. This rivalry is stimulated by structural changes in the world economy, globalisation, and the unravelling international integration. Under these circumstances, success of cities rests on local human resources, flow of information and propensity of local economy for innovation. The main factors of social and economic progress are the followings: Inclination of local economy to structural changes that involves growth and differentiation in the service sector and high tech industries in Hungarian cities; Knowledge-based production and increasing role for local industries of high added value (including traditional sectors of specialised skills); Propensity for innovation and renewal of local economy; Concentration of centres for economic decision-making and strategic planning; Social stability with strong middle class basis (not excluding the possibility of social conflicts as a result of immigration and unemployment); Attractive natural and built environment (including public services of high level); Successful management of local conflicts such as insufficient infrastructure capacities, unemployment and ímmigration; Integration into international and national networks of cities and flow of information, goods, services and persons. Local factors specified above must be established and exploited to set up the basis of permanent innovation and growth of cities to make them successful in a competitive environment.